A very low carbohydrate ketogenic diet increases hepatic glycosphingolipids related to regulation of insulin signalling. (March 2016) - Okuda, Tetsuya; Morita, Naoki
Highlights: KD produced ameliorating effects on metabolic abnormalities found in ob/ob mice. KD increased gangliosides related to regulation of insulin signalling. KD corrected ganglioside levels in ob/ob mouse liver. KD specifically increased insulin resistance-related ganglioside GM3 in WT mouse liver. Abstract: Low carbohydrate ketogenic diet (KD) produces several ameliorating effects against metabolic abnormalities found in obese patients. However, mechanisms underlying the effect of KD are poorly understood. We report here that KD increases gangliosides, which were recently identified as a novel modulator involved in the regulation of cellular insulin signalling. We found that the ob/ob mice had low liver ganglioside content, whereas feeding KD increased this to approximately equivalent levels observed in wild-type mice. This result indicates that KD improves the low level expression of gangliosides in ob/ob mouse liver. On the other hand, feeding KD specifically increased only monosialoganglioside GM3 in wild-type mice. This work revealed the potential utility of low carbohydrate diet including KD as a functional food targeting insulin-related metabolic abnormalities.